Batch copper ion binding and exchange properties of peat - Chen, X.-H.; Gosset, T.; Thevenot, D.R. (Water Research, 1990)
Cupric ion fixation by raw peat is likely involved in both cation exchange with H+, Ca2+, Mg2+ and adsorption-complexation, i.e. fixation of the same equivalent of copper ions and anions (NO3-) without any ion release. The importance of both reactions depends largely on initial copper concentration, peat type and pH. Isotherms of copper (initial concentration ranging between 1 and 20 mM) fixation on two types of peat (eutrophic and oligotrophic peat at 30 g d.w./l at pH ranging between 2 and 4) showed that the higher the initial cupric concentration, the more important is this complexation reaction; over this initial cupric concentration range, ion exchange sites were relatively saturated and reached 308 and 101 mmol/kg d.w. for eutrophic and oligotrophic peat whereas no saturation was found for complexation sites, their capacity attaining up to 74 and 119 mmol/kg d.w., respectively. The apparent equilibrium constant for ion exchange with acid-treated peat (initial pH 4.0, 30 g d.w./l) for various metal binding on both peat sites ranged between 1.1 and 10.8 in 15 mM metallic solutions. The apparent affinity in batch conditions for 5 elements may be compared according to the apparent global equilibrium constants, ranging between 1.1 x 10-6 and 20.2 x 10-6: Pb>Cu>Ca>Mg,Zn for eutrophic peat and Pb>Ca>Cu>Mg,Zn for oligotrophic peat. Cupric ion fixation by raw peat is likely involved in both cation exchange with H+, Ca2+, Mg2+ and adsorption-complexation, i.e. fixation of the same equivalent of copper ions and anions (NO3-) without any ion release. The importance of both reactions depends largely on initial copper concentration, peat type and pH. Isotherms of copper (initial concentration ranging between 1 and 20 mM) fixation on two types of peat (eutrophic and oligotrophic peat at 30 g d.w./1 at pH ranging between 2 and 4) showed that the higher the initial cupric concentration, the more important is this complexation reaction; over this initial cupric concentration range, ion exchange sites were relatively saturated and reached 308 and 101 mmol/kg d.w. for eutrophic and oligotrophic peat whereas no saturation was found for complexation sites, their capacity attaining up to 74 and 119 mmol/kg d.w., respectively. The apparent equilibrium constant for ion exchange with acid-treated peat (initial pH 4.0, 30 g d.w./1) for various metal binding on both peat sites ranged between 1.1 and 10.8 in 15 mM metallic solutions. The apparent affinity in batch conditions for 5 elements may be compared according to the apparent global equilibrium constants, ranging between 1.1 × 10-6 and 20.2 × 10-6: Pb > Cu > Ca > Mg, Zn for eutrophic peat and Pb > Ca > Cu > Mg, Zn for oligotrophic peat.